HUBUNGAN PROMOSI KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN PERILAKU AMAN (SAFE BEHAVIOR) PADA KARYAWAN BAGIAN PRODUKSI PENGOLAHAN MINYAK SAWIT DI PTPN IV KEBUN DOLOK ILIR - riska theodora sipayung; Halinda Sari Lubis; Isyatun Mardiah Syahri (Lingkungan dan Kesehatan Kerja, 2014)
Promoting Occupational Health and Safety among workers, employers, and the community is essential for the company. This is considered important because. Health and Safety Promotion with the main goal pursued labor to fix the safe behavior while working. The purpose of this study is to find out what the relationship between the promotion of Health and Safety with safe behavior on the production employees of palm oil processing PTPN IV Kebun Dolok Ilir. This study is a cross sectional analytic design, the samples are 44 people (random sampling). Analysis of the data used univariate and bivariate analysis using the chi-square test. The results showed most workers ≥ 48 years were 26 persons (59.1%), high school education last at most 30 people (68.2%), the most widely tenure ≥ 17 years for a total of 35 persons (79.5 %), and the majority of employees working in the unit boiler station 7 people (15.9%). Univariate test results obtained by the application of Health and Safety Promotion, namely training and the Health and Safety months activities the majority of respondents said it was bad to the percentage of training as many as 28 people (63.6%) and health and safety months activities as many as 41 people (93.2%) while health and safety signs, monitoring, and health and safety communication majority of respondents expressed either by the percentage of each, health and safety month activities as many as 43 people (97.7%), supervision of as many as 43 people (97.7%), health and safety communication as many as 40 people (90.9%). The results of the chi square test showed there is significant relationship between of health and safety promotion (training and health and safety month activities) with safe behavior with each of p value of 0.007 and 0.034. Suggestions for companies to increase Health and Safety Promotion particularly thorough training specifically to the processing of production employees and involve them in every health and safety months activities to create safe behavior at work. Key Word: Health and Safety Promotion, Safe Behavior